KONTRIBUSI SENI RUPA SEBAGAI DISPLIN ILMU DALAM ISLAM DENGAN AFTERLIFE MAPPING - Parhan, Muhamad; Sukma, Eka Nur Lia; Nugraha, Fikri Ilham; Asofah, Indri; George, Julia Relita; Utama, Karyana Tri (Brikolase : Jurnal Kajian Teori, Praktik dan Wacana Seni Budaya Rupa, 2022)
Fine art is a branch of art that is expressed through visual or visual media that is in close contact with everyday life. However, when the development of science is increasing, there appears a significant gap between art and disciplines in Islam. Whereas art has a very large portion in religion which shows visuals of events in the world and divine signs. The research method uses a qualitative approach by collecting a simple survey of Muslim students or artists in Bandung with an age range of 18-21 years which is carried out online using Google Form. The results show that the contribution of art as a discipline in Islam with afterlife mapping requires an effort to reconstruct educational thinking in order to anticipate any changes that occur: first, what artistic contributions are produced by Muslim artists/students at this time; secondly, do not assume that art makes art performers away from Islamic principles, because this is just a stereotype; Third, make a plan with the contribution you have for the afterlife.